Kedudukan Jaminan Kebendaan Dan Jaminan Pribadi Dalam Perjanjian Modal Ventura Di Indonesia - Edi Wahjuningati (Jurnal Hukum Prasada, 2019)
The joint venture companies are the companies which provide the capital for their business partners. They can obtain the capital from the joint venture companies provided that they possess a good business management, a promising market, a sound cash flow, the devastation mechanism and the existence of their contribution against the national economy. The joint venture companies are required to assist the small – medium skill businesses which posses the difficulty in obtaining the banking credit facilities because the banks prioritize on the collateral aspects. The aim of this research is to know and to analyze the existence of both the property collateral and the personal are in the joint venture agreement and the form of the legal protection against the joint venture companies in securing their invesment. Neither the property collateral nor the personal one is required in the capital sharing agreement among the shareholders in founding the liability limited company ( Ltd ), the expense agreement and in taking the bond conversion; meanwhile the limited capital sharing agreement does not require the property collateral except the personal one. Thus, to protect the joint venture companies which require neither the property collateral nor the personal one in securing their investment can be conducted both preventively and repressively so that they can run their mission well.